Perancangan Desain Kemasan Keripik dengan Menggunakan Metode Quality Function Deployment (QFD) - Zetli, Sri; Tarigan, Elsya Paskaria Loyda; Fajrah, Nofriani (SURYA TEKNIKA, 2024)
The appearance of attractive packaging in a product is something that is a major factor apart from product quality. UMKM Keripik Singkong Usaho still have problems with product packaging which is still simple using ordinary plastic without any labeling. So that research and packaging design are needed using the Quality Function Deployment (QFD) method. The results of the study obtained 18 items that become consumer criteria for the packaging of chips products. The results of the House of Quality show that the greatest desire value of consumers (0.07) for the design of chip packaging is an attractive packaging shape (A1), displaying the expiration date (A7), listing the composition (A10), including the halal logo (A11), packaging materials resistant to oil and water (A12), and the position of the product logo is easy to read (A17). So that the technical criteria are variations in packaging color, variations in writing color, variants of packaging materials, and variants of packaging shapes. The proposed packaging design for the chips has two models, red packaging color for the spicy flavor and green packaging color for the original flavor, where each package includes the expiration date, product composition, and halal logo.